Surgical treatment of severely displaced atrophic jaw fracture: a case report (Research, Society and Development, 2020)
Atrophic mandible fractures usually occur in elderly individuals, in which osteogenesis is decreased, cortical bone is dense and blood supply is decreased. There is a consensus in the literature that the treatment of atrophic mandible fractures remains a major challenge for maxillofacial traumatology, considering the low availability of bone and the morphological and biomechanical characteristics of a toothless mandible. This paper aims to report a case of surgical treatment of bilateral atrophic mandible fracture. The male patient, 61 years old, attended the Oral and Maxillofacial Surgery service, after being the victim of a motorcycle accident, without the use of individual protection materials, evolving with bilateral mandible fracture. On physical examination, the patient had diastasis in the bilateral mandibular body area and in the intraoral examination, ecchymosis was observed in the floor of the mouth. The treatment consisted of an extraoral surgical approach, under general anesthesia, transcervical access, reduction and osteosynthesis of fractured jaw with a 2.4mm locking system plate in each fracture. The therapy allowed the patient to resume his chewing functions with a gain in quality of life. It is concluded that atrophic mandible fractures are uncommon, but with the increase in the elderly population in the coming years, it is expected that its incidence will increase, and it is essential for the maxillofacial surgeon to recognize the available treatment possibilities.